More

    How to find the inverse of a funtion

    How to Find the Inverse of a Function 1

    This is easy — it’s just a list of steps.  At this level, the problems are pretty simple.

    Let’s just do one, then I’ll write out the list of steps for you.

    Find the inverse of f( x ) = -( 1 / 3 )x + 1

    STEP 1:  Stick a “y” in for the “f(x)” guy:

    y = -( 1 / 3 )x + 1

    STEP 2:  Switch the x and y
    ( because every (x, y) has a (y, x) partner! ):

    x = -( 1 / 3 )y + 1

    STEP 3:  Solve for y:

    x = -( 1 / 3 )y + 1 ... multiply by 3 to ditch the fraction ... 3x = -y + 3 ... ditch the +3 ... subtract 3 from both sides ... 3x - 3 = -y ... multiply by -1 ... -3x + 3 = y ... y = -3x + 3

    STEP 4:  Stick in the inverse notation, f^( -1 )( x )

    f^( -1 )( x ) = -3x + 3

    Facebook Comments Box

    Recent Articles

    Related Stories

    Leave a Reply

    Stay on op - Ge the daily news in your inbox

    Facebook Comments Box